Evaluation Of The Application Of Traditional Western Management Theories In Africa From A Survey Of Nigerian Organizations - Akpor-Robaro, M.O.M.; Erigbe, P.A. (Archives of Business Research, 2018)
The paper presents analysis and evaluation of the extent to which traditional theories are adopted and applied in contemporary management practice by Nigerian organizations/managers. To this end,1200 managers of different categories, from different companies were randomly selected for interview in Lagos and Ogun state, Nigeria, through the instrument of questionnaire using the same set of questions. The analysis of the responses reveals that some of the prescriptions of the various theories are being applied unconsciously by some organizations, but many largely depart from the formal framework of existing theories. Most managers did not quite know what theories are, and what theories exist in their areas of management, let alone applying them to making decisions. Evidently most of the managers do not have formal education in management, and most on the job management trainings often fail to expose managers to lessons in management theories and their relevance to management practice. The paper recommends that there is need for management training schools and consultants to emphasize in their programmes, the aspects of theories, to manager trainees, as the basis for good management practice.